Effect of irrigation with saline water on the ordinary chernozem microbial community state - Sviatoslav, Baliuk; Oksana , Naidonova; Olena, Drozd (International Journal of Psychosocial Rehabilitation, 2020)
The effect of irrigation with saline waters on the soil microbial community structure and functioning were studied. Our research was carried out in a long-term stationary field experiment. We identified the biological indices of irrigated soil and its unirrigated analogue. We studied indicators such as: the number of microorganisms belonging to different ecological- functional groups, invertase activity, and cellulose-destroying capacity of soils. To assess the functional state of the microbial community, the following indicators were calculated: oligotrophy and mineralization indices, the total biological index, and the soil biological degradation index. The direction and the degree of change in the biological properties of ordinary chernozem influenced by of irrigation with saline waters have been identified. Irrigation with saline water (total mineralization from 1.2 to 2.2 g/l) of ordinary chernozem (Odessa region, Ukraine) in an intensive mode lasting 12–13 years led to a noticeable suppression of the soil microbial community, a decrease in the number of microorganisms of the main groups on average by 30–40%, increased mineralization processes. The use of land reclamation measures (such as the annual application of phosphogypsum in a dose (3 t/ha) and/or comprehensive measures (3 t/ha of phosphogypsum annually + N150R90K60 + 18 t of manure per hectare of the crop rotation area) enable the regulation of soil biodynamic processes and partial or complete prevention of biological degradation.